Color filter arrays based on dielectric metasurface elements - Berzins, Jonas; Silvestri, Fabrizio; Gerini, Giampiero; Setzpfandt, Frank; Pertsch, Thomas; Baumer, Stefan M. B. (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
Digital imaging has been steadily improving over the past decades and we are moving towards a wide use of multi- and hyperspectral cameras. A key component of such imaging systems are color filter arrays, which define the spectrum of light detected by each camera pixel. Hence, it is essential to develop a variable, robust and scalable way for controlling the transmission of light. Nanostructured surfaces, also known as metasurfaces, offer a promising solution as their transmission spectra can be controlled by shaping the wavelength-dependent scattering properties of their constituting elements. Here we present, metasurfaces based on silicon nanodisks, which provide filter functions with amplitudes reaching 70-90% of transmission, and well suitable for RGB and CMY color filter arrays, the initial stage towards the further development of hyperspectral filters. We suggest and discuss possible ways to expand the color gamut and improve the color values of such optical filters.
CRIS-Team Scopus Importer:2023-04-20
Keywords: CMY; color filter; color filter array; metasurfaces; nanodisk; RGB; silicon